Dementia in Clinical Practice: A Neurological Perspective Pragmatic Studies in the Cognitive Function Clinic - Larner, A. J. (Springer International Publishing, 2018)
This expanded, updated third edition summarizes the pragmatic diagnostic accuracy studies of neurological signs and cognitive and non-cognitive screening instruments undertaken in the author's clinic in the context of day-to-day practice involving patients with cognitive disorders including dementia. A new chapter devoted to comparing and combining instruments is included, and illustrative case studies have been included where relevant. Dementia in Clinical Practice: A Neurological Perspective, Third Edition is a practical resource for medical professionals involved in the assessment and management of patients with dementia and cognitive disorders. It may be of particular interest to neurologists, psychiatrists, geriatricians, primary care practitioners and those working with patients with cognitive impairment in the fields of neuropsychology, psychology, occupational therapy, speech and language therapy and nursing.